Diagnosing dementia in the Arctic: translating tools and developing and validating an algorithm for assessment of impaired cognitive function in Greenland Inuit - I. Kleist; P. Noahsen; O. Gredal; J. Riis; S. Andersen (European Psychiatry, 2022)
Introduction The ageing Arctic populations raise the need for work-up of cognitive function that reflects language and cultural understandings.